Analysis of the curricular methods of teaching standard arabic at the Universidad Autónoma de Madrid (UAM) - El Khaymy, Asmaa (Lenguas Modernas, 2024)
In this study, we aim to examine and analyze some manuals used for teaching Standard Arabic at the Autonomous University of Madrid (UAM). The selected teaching methods for review include: Alatul, Mabruk, and Al Kitaab fi taʿallum al-ʿarabiyya. Our objective is to identify the differences between them, determine their strengths and weaknesses, and evaluate their suitability for teaching Standard Arabic to Spanish students. To achieve this, we will analyze the materials considering various aspects such as their internal and external structure, as well as the content they offer, including grammatical, communicative, phonetic, and cultural elements.